A COMPARATIVE ANALYSIS OF THE ASSOCIATION OF CHRONIC INFLAMMATION VERSUS NO INFLAMMATION ON THE NUTRITIONAL STATUS OF PATIENTS ON CHRONIC MAINTENANCE HEMODIALYSIS - Bano, Uzma; Gondal, Ghulam Murtaza (Journal of Postgraduate Medical Institute, 2012)
Objective: To assess the association of chronic inflammation on the nutritional status of patients onChronic maintenance hemodialysis. Methodology: This cross-sectional comparative study was performed at department of Medicine FaujiFoundation Hospital Rawalpindi. Patients having chronic renal failure who were on regular maintenancehemodialysis for more than 6 months were included in the study. Ultrasound examination was done toconfirm the presence of renal parenchymal disease and shrunken kidneys. The level of C-reactive proteinwas measured as indicator of inflammation and serum albumin, cholesterol level, mid-arm circumference,triceps skin fold thickness, subscapular skin fold thickness and body mass index (BMI) were used as theassessment tools to evaluate the influence of inflammation on the nutritional status in patients. Patient intwo groups with positive or negative CRP were compared regarding the effects of inflammation onnutritional parameters. Results: Out of 30 patients, 13 (43.3%) had evidence of inflammation with positive CRP and a mean BMIof 19.2+3.3 whereas the CRP negative group had a mean BMI of 24.9+1.5. Regarding nutritionalparameters, Triceps Skin Fold Thickness, Subscapular Skin Fold Thickness, mid-arm circumference andserum albumin were also statistically low in CRP positive patients although serum cholesterol levels didnot differ significantly in our study. The CRP positive patients therefore were malnourished as compared tothe CRP negative group. Conclusion: Patients with end stage renal disease on chronic dialysis with evidence of inflammation aremore at risk of malnutrition. Although there is no standardized strategy for the treatment of chronicinflammation in these patients so far but this area needs further research to improve outcome in thesepatients.